Tuning the Solubility of Self-Assembled Fluorescent Aromatic Cages Using Functionalized Amino Acid Building Blocks - Konopka, Marcin; Cecot, Piotr; Ulrich, Sébastien; Stefankiewicz, Artur R. (Frontiers in Chemistry, 2019)
We previously reported novel fluorescent aromatic cages that are self-produced using a set of orthogonal dynamic covalent reactions, operating simultaneously in one-pot, to assemble up to 10 components through 12 reactions into a single cage-type structure. We now introduce N-functionalized amino acids as new building blocks that enable tuning the solubility and analysis of the resulting cages. A convenient divergent synthetic approach was developed to tether different side chains on the N-terminal of a cysteine-derived building block. Our studies show that this chemical functionalization does not prevent the subsequent self-assembly and effective formation of desired cages. While the originally described cages required 94% DMSO, the new ones bearing hydrophobic side chains were found soluble in organic solvents (up to 75% CHCl3), and those grafted with hydrophilic side chains were soluble in water (up to 75% H2O). Fluorescence studies confirmed that despite cage functionalization the aggregation-induced emission properties of those architectures are retained. Thus, this work significantly expands the range of solvents in which these self-assembled cage compounds can be generated, which in turn should enable new applications, possibly as fluorescent sensors.